A case of Mobitz type II atrioventricular block due to Nerium oleander poisoning successfully managed with digoxin-specific Fab antibody fragments - Mustafa Adem Tatlısu; Elif İjlal Çekirdekçi; Şükrü Akyüz; Zekeriya Nurkalem (KARE Publishing, 2015)
Nerium oleander is a popular ornamental plant grown in many tropical and subtropical countries and in the Mediterranean region. It is dangerous because it has been shown to contain several types of cardiac glycosides, and hence can cause cardiac arrhythmias resembling digoxin in their toxicologic manifestations. We report a patient presenting to our hospital with Mobitz type II atrioventricular block after drinking herbal tea prepared from oleander leaves. Three hours after admission, a 200-mg empiric dose of digoxin-specific Fab antibody fragments was administered intravenously over 30 minutes. A 12-lead electrocardiogram (ECG) revealed sinus rhythm at the end of infusion. After 72 hours, the patient was discharged without any symptoms.